2021
DOI: 10.1016/j.bioactmat.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-inspired agarose hydrogel scaffolds for skin tissue engineering

Abstract: Polysaccharide hydrogels are widely used in tissue engineering because of their superior biocompatibility and low immunogenicity. However, many of these hydrogels are unrealistic for practical applications as the cost of raw materials is high, and the fabrication steps are tedious. This study focuses on the facile fabrication and optimization of agarose-polydopamine hydrogel (APG) scaffolds for skin wound healing. The first study objective was to evaluate the effects of polydopamine (PDA) on the mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(89 citation statements)
references
References 55 publications
1
82
0
Order By: Relevance
“…Efficient reconstruction of the function and integrity of the damaged tissues is currently the central focus for their clinical treatment [ 3 ]. Multiple therapeutic options, including novel dressing products [ 4 , 5 ], growth factors [ 6 , 7 ], and bioengineered skin grafts [ 8 ] are available. However, strategies for the regenerative healing of the injured tissues, especially for chronic wounds, remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient reconstruction of the function and integrity of the damaged tissues is currently the central focus for their clinical treatment [ 3 ]. Multiple therapeutic options, including novel dressing products [ 4 , 5 ], growth factors [ 6 , 7 ], and bioengineered skin grafts [ 8 ] are available. However, strategies for the regenerative healing of the injured tissues, especially for chronic wounds, remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the use of collagen-based biomaterials, being the main protein of the ECM, has been widely investigated for tissue engineering studies and showed promising results. As a matter of fact, the application of these biomaterials for the treatment of skin wounds has been reinforced for their characteristics such as biocompatibility [ 16 ], low immunogenicity [ 17 ], and bioactive properties [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, numerous bi-layer dermal substitutes have been developed and applied for the management of full-thickness skin defects, such as Alloderm ® [13,14], Integra ® [15,16], Pelnac ® [17] and Lando ® , of which, the low-layer porous CSS function as DRT. Being the main protein of the extracellular matrix, collagen has excellent biocompatibility with low immunogenicity [18]. In addition, the porous structure guides inward proliferation and the migration of fibroblasts and endothelial cells, which promotes granulation tissue and angiogenesis for WH with less scarring [21,22].…”
Section: Biomaterials Applicationmentioning
confidence: 99%